Evaluation Nurses Practice about Care of Children with Febrile Convulsion - Ali, zainab (Iraqi National Journal of Nursing Specialties, 2022)
Abstract Objective(s): To evaluate the nurses` practices for children who diagnosed with febrile convulsion. Methodology: A quantitative research, descriptive correlational design was used in this study, the study conducted on nurses who work in Al-Diwaniya Pediatrics Teaching Hospital-Iraq for Maternal and Children period from 12th September 2021 to 10th October 2022. A non- probability (convenience) sample has been applied to obtain the study goals. The study sample was (21) nurses who participate in the study. The study tool is composed of two parts: The first part is concerned with collection of nurses socio-demographic data obtained from the nurses by a self-administered questionnaire, while the second part is constructed to assess nurse’s practices about children with febrile convulsion, it consists of (42) closed-ended question. The validity of the study instrument was determined through the (15) of experts in the specialty field. Results: Findings demonstrated assessment of the study sample responses at the nurse’s practices concerning management of children with febrile convulsion in terms of mean and standard deviation. Conclusion: Nurses’ practice abut care of children with febrile convulsion was poor apply. Recommendations: Researcher recommendations periodic in-service training program and regular lectures should be provided to nursing staff in order updating their knowledge and practice about care of children with febrile convulsion. . Keywords: Assessment, Nurses Practices, Febrile Convulsion Children